'Why us?' Causal attributions of childhood cancer survivors, survivors' parents and community comparisons - a mixed methods analysis. (1st February 2019) - Vetsch, J.; Wakefield, C. E.; Doolan, E. L.; Signorelli, C.; McGill, B. M.; Moore, L.; Techakesari, P.; Pieters, R.; Patenaude, A. F.; McCarthy, M.; Cohn, R. J.; ,
Abstract: Introduction: Understanding the cause of their cancer is important for many cancer patients. Childhood cancer survivors'/survivors' parents' beliefs about cancer etiology are understudied. We aimed to assess survivors'/parents' beliefs about what causes childhood cancer, compared with beliefs in the community. We also investigated the influence of clinical and socio-demographic characteristics on the participants' beliefs about cancer etiology. Methods: This two-stage study investigated the participants' beliefs, by using questionnaires assessing causal attributions related to childhood cancer (stage 1) and then undertaking telephone interviews (stage 2; survivors/survivors' parents only) to get an in-depth understanding of survivors'/survivors' parents beliefs. We computed multivariable regressions to identify factors associated with the most commonly endorsed attributions: bad luck/chance, environmental factors and genetics. We analyzed interviews using thematic analysis. Results: Six hundred one individuals (64.6% survivors and 35.4% survivors' parents) and 510 community comparisons (53.1% community adults, 46.9% community parents) completed the question on causal attributions. We conducted 87 in-depth interviews. Survivors/survivors' parents (73.9%) were more likely to believe that chance/bad luck caused childhood cancer than community participants (42.4%). Community participants more frequently endorsed that genetics (75.3%) and environmental factors (65.3%) played a major role in childhood cancer etiology (versus survivors' and survivors' parents: genetics 20.6%, environmental factors: 19.3%). Community participants, participants with a first language other than English, and reporting a lower quality of life were less likely to attribute bad luck as a cause of childhood cancer. Community participants, all participants with a higher income and higher education were more likely to attribute childhood cancer etiology to environmental factors. Conclusion: Causal attributions differed between survivors/survivors' parents and community participants. Most of the parents and survivors seem to understand that there is nothing they have done to cause the cancer. Understanding survivors' and survivors' parents' causal attributions may be crucial to address misconceptions, offer access to services and to adapt current and future health behaviors.